Policing firearm violence: Examining space-time associations between shootings and firearm arrests to gauge police responsiveness. Issue 1 (11th March 2014) - Wyant, Brian
Abstract : Purpose: – The purpose of this paper is to generate information about the contours of police responsiveness, focussing on how quickly and precisely police make firearm arrests after a shooting incident. Design/methodology/approach: – Using a modified version of the Knox close pair method, a spatio-temporal clustering technique, over 11, 000 shooting incidents and firearm arrests between 2004 and 2007 in Philadelphia, PA were analyzed. Findings: – Police are responding quickly and in a geographically targeted fashion to shootings. Across Philadelphia elevated patterns of firearm arrests were approximately two and a half times greater than would be expected if shootings and firearm arrests lacked a spatio-temporal association. Greater than expected patterns of firearm arrests persisted for roughly one-fourth of a mile and for about one week from the shooting incident but the strength of these associations waned over space and time. The pattern of police response varied slightly across different police divisions. Research limitations/implications: – The current method uncovered spatio-temporal patterning and determined when these patterns were significantly different from what would be expected if the events were completely independent. Specific events and processes surrounding each event are not known. Practical implications: – Findings can help inform the knowledge about police behavior in terms of how police produce arrests. Originality/value: – The patterns observed here provide more micro-level detail than has been revealed in previous studies regarding police responsiveness to firearm violence while also introducing a more integrated spatially and temporally specific framework.